2010
DOI: 10.4244/eijv5i6a125
|View full text |Cite
|
Sign up to set email alerts
|

Tako-Tsubo syndrome and reversible epicardial coronary spasm

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Interestingly, coronary vasospasm has also been reported with other unusual presentations like severe arrhythmias or even Tako-Tsubo syndrome. 7 However, in our patient a completely normal left ventricular function was demonstrated. To the best of our knowledge, this is the first case of asymptomatic variant angina that is diagnosed incidentally as a consequence of other acute clinical entity that precipitates coronary vasospasm.…”
Section: Discussioncontrasting
confidence: 48%
“…Interestingly, coronary vasospasm has also been reported with other unusual presentations like severe arrhythmias or even Tako-Tsubo syndrome. 7 However, in our patient a completely normal left ventricular function was demonstrated. To the best of our knowledge, this is the first case of asymptomatic variant angina that is diagnosed incidentally as a consequence of other acute clinical entity that precipitates coronary vasospasm.…”
Section: Discussioncontrasting
confidence: 48%
“…Moreover, the first cases of takotsubo cardiomyopathy suggested coronary vasospasm as the underlying cause of apical myocardial dysfunction [11]. Furthermore, recent reports indicate that coronary vasospasm can act as a trigger for myocardial stunning compatible with the takotsubo syndrome [17, 18]. In our patient, we hypothesize that coronary vasospasm was the major trigger for developing reversible myocardial dysfunction of the LV-apex, compatible with takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 54%
“…18 Indeed, severe, subocclusive epicardial coronary artery spasm occurred in these patients, associated with typical echocardiographic transient left ventricular dysfunction, as classically observed in takotsubo syndrome. 19 Similarly, Tinti et al 20 described the syndrome in a 61-year-old woman with chest pain, ST-segment elevation, and increase in troponin I and creatine kinase-MB who had angiographic evidence of a diffuse spasm of the anterior interventricular artery below the first septal branch, which resolved by intracoronary verapamil (Figure 3). 20 Coronary microvascular abnormalities may represent another cause of takotsubo syndrome.…”
Section: Pathogenic Factorsmentioning
confidence: 94%
“…19 Similarly, Tinti et al 20 described the syndrome in a 61-year-old woman with chest pain, ST-segment elevation, and increase in troponin I and creatine kinase-MB who had angiographic evidence of a diffuse spasm of the anterior interventricular artery below the first septal branch, which resolved by intracoronary verapamil (Figure 3). 20 Coronary microvascular abnormalities may represent another cause of takotsubo syndrome. Generalized increase in coronary microvascular resistance can lead to altered coronary perfusion in takotsubo syndrome patients, as shown by Bybee et al, 21 who observed Thrombolysis In Myocardial Infarction (TIMI) frame count abnormalities in all 3 main coronary arteries in their patients.…”
Section: Pathogenic Factorsmentioning
confidence: 94%